Concurrent design of a lower limb rehabilitation mechanism - Muñoz Reina, José Saúl; Villarreal Cervantes, Miguel Gabriel; Corona Ramirez, Leonel German; Castro Medina, Robero (Enfoque UTE, 2018)
The rehabilitation given by robotic systems is a choice for minimizing the recovery time of a patient and boost their muscular and skeletal capacity on a limb damaged. However, the high cost of these systems limits patients to receive these kind of treatments. The systems of one degree of freedom are a low cost alternative to health care and rehab at home. In this paper, the structural design of an 8-link mechanism for the rehabilitation of lower limbs is performed, based on the approach and solution of an optimization problem in which certain objectives are met, such as dimensional synthesis, and the minimizing of torque to make control easier.